Feasibility Evaluation of Wastewater Treatment Plant System: A Case Study of Domestic Wastewater System in Sleman Regency, Yogyakarta, Indonesia - Sri Puji Saraswati; Gregorius Henry Diavid; Sophia An Nisa; Nilna Amal; Visi Asriningtyas (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
Domestic Wastewater Treatment Plant (DWWTP) type 1 and DWWTP type 2 were being evaluated. DWWTP type 1 is located in Sembir area while DWWTP type 2 is located in Tambakrejo area which are both in Sleman Regency, Special Region of Yogyakarta (Daerah Istimewa Yogyakarta or DIY), Indonesia. The emphasis of this research is to choose the manhole material which has the least leakage to the soil, influent discharge performance and wastewater treatment quality effluent. The method used to measure the discharge was by averaging daily discharge for twelve hours, while the E. Coli bacteria under the manhole was also being analyzed. Pollution Index method was also used to evaluate the pollution levels of the wastewater treatment effluent. Results of the study indicated that DWWTP type 1 performance was not optimal because the number of users was greater than that of the design. The impacts were excessive capacity, improper detention time and several parameters of the effluent did not meet the Indonesian legal regulation, including Chemical Oxygen Demand (COD), with efficiency of 34.43%. Wastewater treatment quality effluent parameters which met the Indonesian legal regulation were pH, TSS, TDS, Oil and Grease and Chlorine for DWWTP type 1. Pollution Index (PI) of DWWTP type 1 was 7.02 and PI of DWWTP type 2 was 6.96 which were relatively categorized as moderately polluted. DWWTP type 2 performance was optimal with mean discharge lower than the design discharge. Parameters of the effluent which met the Indonesian legal regulation were pH, TSS, TDS, Oil and Grease, Detergent and COD for DWWTP type 2. The COD of DWWTP type 2 met the Indonesian legal regulation with high efficiency of 73.24%. The E. Coli bacteria was not found in soils under the ring type precast concrete manholes. Hence ring type precast concrete base manhole is recommended.